2020
DOI: 10.2139/ssrn.3574024
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of STEM Project Based Learning on Self-Efficacy Among High-School Physics Students

Abstract: Science, Technology, Engineering and Mathematics (STEM) Project-Based Learning (PjBL) is increase effectiveness, create meaningful learning and influence student attitudes in future career pursuit. There are several studies in the literature reporting different aspects of STEM into a PjBL pedagogy. However, the effect of implementing STEM PjBL in terms of improving students' skills in self-efficacy levels in physics mechanics at high school level has not been demonstrated as expected in the previous literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
2
2
0
Order By: Relevance
“…Self-efficacy mediates the relationship between the STEM learning model and student learning outcomes. This is corroborated (Samsudin et al, 2020) STEM Method to Improve Students' Ability to Solve Problems.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Self-efficacy mediates the relationship between the STEM learning model and student learning outcomes. This is corroborated (Samsudin et al, 2020) STEM Method to Improve Students' Ability to Solve Problems.…”
Section: Resultssupporting
confidence: 55%
“…The confidence gained by participation in STEM-related activities is invaluable. Students should develop a growth mindset by viewing their homework as a challenge, and then working diligently to complete it by using their analytical and problem-solving skills (Samsudin et al, 2020). Students who believe in their own abilities to do tasks successfully have high self-efficacy (Jamali et al, 2015).…”
Section: A Introductionmentioning
confidence: 99%
“…Environmental Education is necessary to ensure the preservation of the environment and make learning more meaningful. This aligns with research by Samsudin (2020) which states that physics education using social and environmental-based teaching models can increase students' activity levels (Samsudin et al, 2020). Furthermore, another study by Satriawan (2021) also explains that to address technological and scientific advancements, there is a need for educational planning that can enhance 21st-century knowledge and skills simultaneously (Satriawan et al, 2021).…”
Section: Introductionsupporting
confidence: 59%
“…These methodologies aim to not just impart abstract mathematical concepts but to contextualize them within practical, real-life scenarios, thereby fostering a deeper and more meaningful learning experience (Dahl, 2018;Perrenet et al, 2000;Roh, 2003). Research has also demonstrated positive correlations between problem-based learning and students' attitude towards mathematics as well as their own potential (Boaler et al, 2022), students' self-efficacy in problem-solving (Samsudin et al, 2020), creativity (Roble et al, 2021), and motivation and knowledge transfer (Rezaei & Asghary, 2024).…”
Section: Literature Reviewmentioning
confidence: 99%